Internalizing-type and externalizing-type problems in school children : a comparison of those with attention deficit hyperactivity disorder (ADHD) and learning disorder (LD) and an exploration of gender differences. - Lee, Deborah Lee Chen. (2011)
This study assessed the internalizing-type and externalizing-type problems experienced by school going children with ADHD or LD, based on information from an archival dataset of 220 Singaporean children/adolescents, aged 5 to 17 years old. Results showed that children with ADHD scored significantly higher on externalizing-type problems than children with LD while children with LD scored significantly higher on internalizing-type problems than children with ADHD. Additionally, gender differences were examined and males and females generally did not differ significantly in their ratings on internalizing-type and externalizing-type problems. No significant interactions of diagnostic grouping and gender were found with regard to internalizing-type and externalizing-type problems. Findings emphasize the need for education to incorporate mental health services for children with ADHD or LD.